Mengubah Pemahaman Konsep Istikharah Dari Bertanya Menuju Berserah Diri - Alexa Ayu Dewanda; Intan Nuraini Azzahra; Hanestesia Zahara; Wismanto Wismanto; Resya Eka Putri (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This article is an interpretive study of the Istikharah prayer taught by the Prophet Muhammad SAW as mentioned in several hadith histories. Through the content analysis method, the author tries to examine the meaning of prayer using descriptive analysis methods. From this analysis, information was obtained that there must be a change in understanding of the concept of Istikharah which is often understood as a form of "asking" Allah what the best option is. The change in question – which does not evaluate current understanding – is to understand that Istikharah is the process of activating tawakal. It contains istikhār, istiqdār and istifdāl. Istikhār is a request to choose the best based on Allah's knowledge, starting from the awareness that He is All-Knowing while we do not know. Istiqdār is a request for the best destiny based on Allah's power, because He is Almighty while we are helpless. Istifdāl is a request for great grace. The next process is taukil al-amr (presentation of work) to Allah. If it is good, then it is delicious, easy to do and a blessing. If it's bad, turn away, look towards something better and be happy with His fate. This understanding will lead us to the conclusion that the best attitude of Istikharah is hūsn al-zānn (good prejudice) towards God and satisfaction with His destiny.